Nipple Loss following Nipple-Sparing Mastectomy. Issue 1 (July 2016) - Mastroianni, Melissa; Lin, Alex M.; Smith, Barbara L.; Austen, William G.; Colwell, Amy S.
Abstract : Background: Nipple preservation at the time of mastectomy is increasingly performed to enhance the overall result from the reconstruction. Unfortunately, some of these patients may lose their nipples for oncologic reasons or because of necrosis. Several studies have investigated risk factors associated with nipple loss, but few data exist on the incidence of cancer in the nipple specimen, nipple removal for cosmesis or symmetry, and whether these patients subsequently pursue nipple reconstruction. Methods: A retrospective review was performed on nipple-sparing mastectomies and immediate reconstruction from 2007 to 2013. Results: Of 443 patients (775 breasts), 51 nipples (6.6 percent) were removed. Of the 51 nipple losses, 76 percent had total nipple or nipple-areola complex loss and 24 percent had partial loss. Twenty-five of the nipples (49 percent) required excision for oncologic reasons, 18 nipples (35 percent) were either partially or totally lost because of necrosis, and one nipple (2 percent) was excised for cosmetic reasons. In cases of bilateral reconstruction and unilateral nipple loss, 65 percent of contralateral normal nipples were retained and 35 percent ( n = 7) were removed for symmetry. Fourteen nipples had residual cancer or atypia, whereas 37 had normal pathologic findings. Twenty-one nipples (40 percent) were reconstructed and 30 were not. Conclusions: In this series, the incidence of nipple loss following nipple-sparing mastectomy was 6.6 percent and related primarily to positive oncologic margins. The rate of removal for cosmesis was low, suggesting that for most patients the nipple lies in an acceptable position. After removal, 40 percent of patients had nipple reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.